Cáncer de mama en varón de presentación atípica - Yan-Quiroz, Edgar F. (2024)
Breast cancer is a rare neoplasm in men and represents 1% of all breast cancers. Its low prevalence and the limited knowledge of physicians about this disease generates a diagnosis in advanced stages. We present the case of a 44-year-old male patient with a long-lasting tumor in the sternal region, whose delayed clinical and histopathological diagnosis favored the progression of the disease to the right axillary region, delaying his treatment. He received radiotherapy and adjuvant chemotherapy, as well as trastuzumab therapy, with tolerability.